Effect of food colorants on color of denture base acrylic resins - Sunil Kumar Vaddamanu; Rajesh Vyas; Sourav Kumar Pati; Radhika Thakkar; Amit Kumar; Bhumika Kamal Badiyani (Wolters Kluwer Medknow Publications, 2021)
Background: Acrylic resin has been successfully used for complete denture fabrication for many years. Color stability is very crucial clinical properties for dental materials, and color change may be an indicator of aging or damaging of materials. Aim and Objectives: This study has been designed to determine the color stability of heat cure denture base acrylic resins in commonly consumed solutions causing stains. Methodology: Four hundred disc samples of four commercially used heat cure denture base resins (Trevalon®, DPI®, Veracril®, and Pyrax®) were fabricated (100 in each group). These were checked for any change in optical density by immersing them in four different staining solutions (tea, coffee, turmeric, and betel leaf, i.e., paan) and synthetic saliva for 1-month synthetic saliva was taken as control. The denture cleansers were also evaluated for their efficacy determined by their ability to remove the stains caused by the staining solutions. Results: It was observed that Trevalon® showed least change in optical density and coffee illustrated the maximum potential for staining the denture base resins and is the most difficult to be removed using a denture cleanser. Conclusion: It can be concluded that Trevalon® demonstrated maximum color stability. Among the staining solutions, coffee caused maximum stains.